Copper(I) and silver(I) homometallic complexes of new bis(2,2′-bipyridine) ligands - Beer, P; Wheeler, J; Moore, C (1992)
New ligand systems containing two 2,2′-bipyridin-6-ylmethyl moieties linked via 1,4,10,13-tetraoxa-7,16-diazacyclooctadecane, 1,4,10,13-tetrathia-7,16-diazacyclooctadecane, 4,4′-bipyridinediium, N,N′,N″-tritosyldiethylenetriamine and toluene-p-sulfonamide spacer units have been prepared. A variety of homometallic Copper(I) complexes have been isolated and fast atom bombardment mass spectrometry investigations suggest most of the complexes to be of general formula [Cu2L2][PF6]2. Solution 1H NMR spectra of these species imply the existence of additional complex components of 1:1 L:copper(I) ratio. A variety of mono- and bi-metallic silver(I) complexes were also isolated with these ligands.